PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 028 SINTONG KECAMATAN TANAH PUTIH - Samidi, Samidi; Zulkifli, Zulkifli; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve IPA student learning outcomes Class IV SDN 028 Sintong Tanah Putih Rokan Hilir with the implementation of cooperative learning model type Student Teams Achievement Divisions (STAD). This study is the subject of the fourth grade students of SDN 028 Sintong Tanah Putih, amounting to 26 people with 13 male students and 13 female students. Data collection instruments in this study is the activities sheet teacher, student activities sheets and achievement test. This study presents the results obtained from the value of learning semester before action with an average 64.23 and after the action increased in UH I in Cycle I to 70.19. In the UH II Cycle II increased again to 74.23. The activities of teachers in the learning process cycle I, the first meeting IS 54.2% and at the second meeting increase to 58.3%. At the first meeting of the cycle II, teacher activities increased to 79.2% and in the second meeting of cycle II increased to 95.8%. Similarly, analysis of student activitie at the first meeting of cycle I was 45.8% and increased in the second meeting of the cycle I to 58.3%. At the first meeting of cycle I of student activities is 79.2% and in the second meeting of cycle II increased to 91.7%. The research results of fourth grade SDN 028 Sintong Tanah Putih prove that the application of cooperative learning model Student Teams Achievement Divisions (STAD) can improve learning outcomes IPA Grade IV SDN 028 Sintong Tanah Putih.Keywords: Cooperative Learning Model Type Student Teams Achievement Divisions (STAD), IPA Learning Outcomes